Effectiveness of resistance training to improve muscle strength and physical performance of patients with diabetes mellitus: a meta-analysis - Babae, Priscilla Mary Ntim; Dadzie, Awurabena Quayeba; Ruku, Denny Maurits (Jurnal Ners, 2025)
Introduction: Metabolic disorders in diabetes mellitus (DM) sufferers, caused by insulin resistance, chronic muscle inflammation, and mitochondrial dysfunction, can affect muscle structure and function and reduce physical performance (PP). Thus, rehabilitation in the form of resistance training (RT) is needed to overcome these problems. This study aims to determine the effect of RT on muscle strength (MS; lower and upper limbs) and PP (primary outcome), as well as body mass index (BMI), VO2 peak, lean muscle mass, HbA1c, blood pressure (BP), and adverse events (secondary outcome) in patients with DM. Methods: Six databases were used in a comprehensive search conducted from March to April 2025 to locate relevant articles. We used Standard Mean Difference (SMD), Mean Difference (MD), and Risk Difference with a 95% Confidence Interval (CI), to determine the effect of RT. We assess the quality of studies using the Joanna Briggs Institution checklist. Results: 26 articles randomized controlled trial articles were included, showing that RT has a significant effect on improving MS (lower and upper limbs), PP (primary outcome), and VO2 peak, LMM (secondary outcome); Additionally, RT has a significant effect in lowering HbA1c and systolic blood pressure (SBP), but not significantly in reducing diastolic blood pressure (DBP) (secondary outcome) between the intervention group and control group of patients with DM. There were no RT-related adverse events. Conclusions: RT is a rehabilitation recommendation to improve MS and PP and is also a rehabilitative effort for those living with DM.